Inoculation with cyanobacteria and co-inoculation with Azospirillum brasilense on phytometrics characteristics of maize (Bioagro, 2020)
Cyanobacteria can fix atmospheric N and transform it into available forms for crops, which has increased interest in their use as inoculants. Our objective was to evaluate the influence of inoculation with cyanobacteria and co-inoculation with Azospirillum brasilense on phytometrics characteristics of maize. Two greenhouse trials were conducted; in the first, we tested the effect of inoculation (I) with Nostoc muscorum, Anabaena sp. Anabaena cylindrica, Calothrix brevissima and A. brasilense, with and without N fertilization (F) on plant and ear height, stem diameter, root volume, leaf area, biomass of root, stem and leaf, and foliar content of chlorophyll and N, P, K, on corn variety IPR164; in the second, the effect of co-inoculation with these cyanobacteria and A. brasilense on the mentioned variables in two maize genotypes (variety IPR 164 and hybrid DOW 2B587) was evaluated. In the first trial there were significant isolated effects for I and F but the interaction I x F was only significant for the leaf area; the inoculation caused increases on growth variables and content of chlorophyll b; the most effective inoculation treatments were with N. muscorum and A. cylindrica. In the second trial, the co-inoculation with A. cylindrica + A. brasilense caused the best response, independently of the genotype. These results show a stimulating effect of cyanobacteria to promote growth in maize.
Keywords: Anabaena sp; Calothrix brevissima; diazotrophic bacteria; Nostoc muscorum; Zea mays